Scheduling Jobs with Release and Delivery Times Subject to Nested Eligibility Constraints - Zhang, Yu-Zhong; Li, Shu-Guang (Journal of the Operations Research Society of China (Internet), 2021)
The problem of scheduling jobs with release and delivery time subject to machine eligibility constraints is considered. The eligible sets of the jobs are nested, and preemptions are not allowed. The goal is to minimize the maximum delivery completion time, i.e., the time by which all jobs are delivered. For the special case of equal release time, a 2-approximation algorithm is presented whose running time depends linearly on the number of jobs. For the general case of unequal release time, a polynomial time approximation scheme is derived.